Examining the impact of perceived stress, anxiety, and resilience on depression among medical staff after COVID-19 quarantine: a chain mediation analysis - Dongyang Chen; Yi Ni; Jiani Lu; Yiwen Wang; Qi Qi; Hua Zhai (Frontiers Media S.A., 2023)
IntroductionThe COVID-19 pandemic and subsequent quarantine measures have led to a significant impact on mental health worldwide. Medical staff, in particular, have been exposed to high levels of stress due to their frontline work during the crisis. However, there is still limited research on the psychological mechanism among medical staff after quarantine.MethodsIn this cross-sectional observational study, 150 medical staff from Shanghai YangZhi Rehabilitation Hospital, Shanghai, China, were enrolled in October 2022. SPSS 26.0 and PROCESS 4.0 model 6 were used to analyze the chain mediating effect of perceived stress, anxiety, resilience and depression among medical staff after quarantine. Anxiety and depression were compared during and after the quarantine. All scales have high validity and reliability in a Chinese population.ResultsOur findings revealed a positive correlation between perceived stress and anxiety (r = 0.60, p < 0.001) and depression (r = 0.60, p < 0.001) levels among medical staff. Conversely, resilience was found to have a negative correlation with perceived stress (r = −0.67, p < 0.001), anxiety (r = −0.57, p < 0.001) and depression (r = −0.61, p < 0.001). The score of depression during the quarantine was higher than the score after the quarantine, but the p-value is only marginally significant (p = 0.067). The score of anxiety during the quarantine was significantly higher than the score after the quarantine (p < 0.05). Moreover, the chain mediation model suggested that anxiety and resilience could mediate the association between perceived stress and depression among medical staff following quarantine. Specifically, perceived stress had no direct effect on depression (β = 0.025, t = 0.548, p = 0.59) but positively predicted anxiety (β = 0.381, t = 8.817, p < 0.001) and resilience (β = −1.302, t = −6.781, p < 0.001), which influenced depression levels indirectly through multiple pathways. The three indirect paths: the mediating role of anxiety, the mediating role of resilience, and the chain mediating role of both anxiety and resilience.DiscussionThis study emphasizes the importance of psychological interventions aimed at protecting medical staff's psychological resilience and promoting coping mechanisms to manage stress during and after crises such as the COVID-19 pandemic. Additionally, our findings suggest that both anxiety and resilience play critical roles in mitigating the detrimental effects of perceived stress on mental health and further highlight the need for continued research to better understand the complex interplay of these factors.